التطاول على الفتوى ومظاهر انتشار الأقوال الشاذة في بلاد يوربا النيجيرية: Factors and Solutions for Strange Religious Verdicts in Yorubaland of Nigeria - Ahmad Arikewuyo, Nafiu; Bolajoko, Habeebullah Yusuf (Al-Basirah Journal, 2024)
Fatwa enjoys an enviable position among the Muslims, most especially the jurists who are saddled with the responsibility of issuing religious verdicts to evolving social, economic and political matters. Resulting from this, the sensitivity of issuing verdict and its need for regulation cannot be underestimated. More so, the negative impact of unregulated fatwas on causing rancor and social instability cannot be glossed over. Against this backdrop, this research aims to study this manifestation, using Yorubaland in Nigeria, a region with majority of Muslim population as case study. The study adopts analytical method of research. The study shows that issuing strange fatwa is not peculiar to a particular school of thought in the region; rather both the Sufi and Salafi scholars are guilty of the menace. It also highlights some causes of this phenomenon which include lack of considering the peculiarity of societies, non-specialization in Shari’ah and giving priority to ideological inclination above objectivity. The study recommends collective fatwa issuing as a lasting solution for the menace of strange fatwas in Yorubaland of Nigeria.